Evaluation of Diverse Microalgal Species as Potential Biofuel Feedstocks Grown Using Municipal Wastewater - Hiibel, Sage R.; Lemos, Mark S.; Kelly, Brian P.; Cushman, John C. (Frontiers in Energy Research, 2015)
Microalgae offer great potential as a third-generation biofuel feedstock, especially when grown on wastewater, as they have the dual application for wastewater treatment and as a biomass feedstock for biofuel production. The potential for growth on wastewater centrate was evaluated for forty microalgae strains from fresh (11), brackish (11), or saltwater (18) genera. Generally, freshwater strains were able to grow at high concentrations of centrate, with two strains, Neochloris pseudostigmata and N. conjuncta, demonstrating growth at up to 40% v/v centrate. Fourteen of eighteen salt water Dunaliella strains also demonstrated growth in centrate concentrations at or above 40% v/v. Lipid profiles of freshwater strains with high-centrate tolerance were determined using gas chromatography-mass spectrometry (GC-MS) and compared against those obtained on cells grown on defined maintenance media. The major lipid compounds were found to be palmitic (16:0), oleic (18:1), and linoleic (18:2) acids for all freshwater strains grown on either centrate or their respective maintenance medium. These results demonstrate the highly concentrated wastewater can be used to grow microalgae, which limits the need to dilute wastewater prior to algal production. In addition, the algae produced generate lipids suitable for biodiesel or green diesel production.